Enhanced electrochemical performance of Li2.72Na0.31MnPO4CO3 as a cathode material in "water-in-salt" electrolytes. Issue 95 (17th November 2021) - Xie, Baowei; Sakamoto, Ryo; Kitajou, Ayuko; Zhao, Liwei; Nakamoto, Kosuke; Okada, Shigeto; Albrecht, Ken; Kobayashi, Wataru; Okada, Masaki; Takahara, Toshiya
Abstract : A full cell composed of ion-exchanged Li2.72 Na0.31 MnPO4 CO3 from Na3 MnPO4 CO3 and LiTi2 (PO4 )3 with a water-in-salt electrolyte exhibites operation voltage of approximately 1 V. Abstract : A carbonophosphate compound of Li2.72 Na0.31 MnPO4 CO3 was synthesized via ion exchange. The initial discharge capacity of Li2.72 Na0.31 MnPO4 CO3 in 15 molal (or 15 m) LiTFSI was 110 mA h g −1 at 2 mA cm −2 (∼0.5C). Due to the decomposition of Li2.72 Na0.31 MnPO4 CO3, the capacity retention degraded to 64% after 100 cycles.